Hubungan Kekerasan Verbal dengan Kepercayaan Diri pada Anak Usia Sekolah di UPTD SPF SDN Cindogo 1 Kabupaten Bondowoso - Zaidhane, Joan Franco Abrar Dzulfi (Yayasan Mandar Indonesia, 2025)
School-aged children are vulnerable to verbal abuse in educational settings, which can have more serious consequences than physical abuse because it damages mental health and self-confidence. Verbal abuse of school-aged children needs to be addressed immediately because it can damage self-confidence and disrupt emotional and social development at a crucial stage of character formation. A preliminary study at UPTD SPF SDN Cindogo 1 in Bondowoso Regency indicated low self-confidence among students due to verbal abuse. This study aims to analyze the relationship between verbal abuse and self-confidence in school-aged children at UPTD SPF SDN Cindogo 1 in Bondowoso Regency. This study employs a quantitative correlational cross-sectional design. The study population and sample consist of all students at UPTD SPF SDN Cindogo 1 in Bondowoso District, totaling 97 respondents, using total sampling technique. Data were collected through verbal abuse and self-confidence questionnaires, then analyzed univariately and bivariately using the Spearman Rho test with a significance level of α=0.05. It was found that 65% of students experienced moderate verbal abuse, and 35% experienced severe verbal abuse. Regarding self-confidence levels, 56% had moderate self-confidence, 29% had low self-confidence, and 15% had high self-confidence. The Spearman Rho test yielded a p-value of 0.000 (<0.05), indicating a significant relationship. The correlation coefficient obtained was -0.343, indicating a moderate, significant negative correlation between verbal abuse and self-confidence among school-aged children at UPTD SPF SDN Cindogo 1 in Bondowoso District. An increase in verbal aggression is correlated with a decrease in self-confidence. Fostering empathy and making schools safe and enjoyable places will have a positive impact on their mental and social development.